A STUDY ON PROPORTIONAL ANALYSIS OF CUSTOMER SATISFACTION SURVEY AMONGST ORGANIZED RETAIL FORMATS IN VISAKHAPATNAM - Vanaja, Dr. Jonnalagadda; Chenna Keshav, Chinthakindi; Ujjvala, Hanumanthu; Abhishek, Kolla (The journal of contemporary issues in business and government, 2022)
The service sector is one of the fastest expanding sectors in the global economy that contribute the lion’s share to support nations’ GDP, and it is one of the areas where research on innovation has received a lot of attention. The purpose of the research was to study the customer satisfaction survey amongst organized retail formats in Visakhapatnam. Customer who are delighted also likely to tell others of their favorable experiences and thus engage in positive or direct promotion of outlets. The sample study consist of 100 respondents, Samples collected from Reliance trends, Life style, Shoppers stop, Spencer and Big bazaar. The study was conducted between January to March 2022. Customer satisfaction does have a positive effect on an organization's profitability, satisfied customers form the foundation of any successful business as customer satisfaction leads to repeat purchases, brand loyalty, and positive word of mouth. Satisfied customers are most likely to share their experiences with other people to the order of perhaps five or six people. Equally well, dissatisfied customers are more likely to tell another ten people of their unfortunate experience.